2010
DOI: 10.1073/pnas.0914440107
|View full text |Cite
|
Sign up to set email alerts
|

African great apes are natural hosts of multiple related malaria species, including Plasmodium falciparum

Abstract: Plasmodium reichenowi, a chimpanzee parasite, was until very recently the only known close relative of Plasmodium falciparum, the most virulent agent of human malaria. Recently, Plasmodium gaboni, another closely related chimpanzee parasite, was discovered, suggesting that the diversity of Plasmodium circulating in great apes in Africa might have been underestimated. It was also recently shown that P. reichenowi is a geographically widespread and genetically diverse chimpanzee parasite and that the world diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
223
1
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 233 publications
(242 citation statements)
references
References 28 publications
12
223
1
3
Order By: Relevance
“…The chimpanzee samples proved to be extremely diversified. Two samples (CPZcam46 and CPZcam137) cluster with P. falciparum, suggesting that this parasite is present not only in gorillas, as already shown by Prugnolle et al (29) and as observed by us, and in bonobos (30), but also in chimpanzees. A third chimpanzee sample (CPZcam61) appears to be P. reichenowi, and two others (CPZcam80 and CPZcam155) associate with P. gaboni.…”
Section: Resultssupporting
confidence: 61%
See 3 more Smart Citations
“…The chimpanzee samples proved to be extremely diversified. Two samples (CPZcam46 and CPZcam137) cluster with P. falciparum, suggesting that this parasite is present not only in gorillas, as already shown by Prugnolle et al (29) and as observed by us, and in bonobos (30), but also in chimpanzees. A third chimpanzee sample (CPZcam61) appears to be P. reichenowi, and two others (CPZcam80 and CPZcam155) associate with P. gaboni.…”
Section: Resultssupporting
confidence: 61%
“…One gorilla sample (GGcam10) belongs within the P. falciparum cluster, thus confirming the presence of P. falciparum-related parasites in gorillas, as reported by Prugnolle et al (29). The second gorilla sample (GGcam13) appears to be closest to P. gaboni, although statistically not closer to gaboni than to the falciparum-reichenowi clade.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…Murray et al 2013). Les agents pathogènes et les anticorps produits contre ces agents peuvent être décelés dans les échantillons de fèces Kaiser et al 2010 ;Köndgen et al 2010 ;Prugnolle et al 2010 ;Reed et al 2014). La salive trouvée sur un aliment partiellement consommé et abandonné peut fournir des informations sur des agents pathogènes spécifiques (Schaumburg et al 2013 ;Smiley Evans et al 2015).…”
Section: Suivi De La Santé Et Surveillance Des Maladiesunclassified